Wybrane metody analizy zależności kosztów od wielkości produkcji - Jędruchniewicz, Andrzej (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1999)
An individual firm aiming at the most effective use of production factors is interested in the level of its production costs. Thus, these costs are subject to steady economic analysis. The paper deals with production costs changes caused by changes in one selected factor (output quantities) holding the other factors constant. Very useful in an assessment of the relation between two above mentioned variables are statistical and econometric methods, for example indexes and econometric models. Indexes help to compare the dynamics of change in analysed economic determinants. On the contrary, a key role in presentation of quantitative relations between examined variables, is played by econometric models. Additionally, they have application in cost prediction. The purpose of this study was to present selected methods and their use in the case of chosen enterprise. Both indices and econometric models might enrich a set of analytical methods applied by firms and in consequence, extend the scope of conducted analysis.